If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5z + 8.6 = 4.8z Reorder the terms: 8.6 + 0.5z = 4.8z Solving 8.6 + 0.5z = 4.8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4.8z' to each side of the equation. 8.6 + 0.5z + -4.8z = 4.8z + -4.8z Combine like terms: 0.5z + -4.8z = -4.3z 8.6 + -4.3z = 4.8z + -4.8z Combine like terms: 4.8z + -4.8z = 0.0 8.6 + -4.3z = 0.0 Add '-8.6' to each side of the equation. 8.6 + -8.6 + -4.3z = 0.0 + -8.6 Combine like terms: 8.6 + -8.6 = 0.0 0.0 + -4.3z = 0.0 + -8.6 -4.3z = 0.0 + -8.6 Combine like terms: 0.0 + -8.6 = -8.6 -4.3z = -8.6 Divide each side by '-4.3'. z = 2 Simplifying z = 2
| 72/32 | | 13.7y=6.2+30 | | 0.5z+8.6z=4.8z | | 0.007x+0.03=0.01 | | 3/4x-2-4(1/2x-2) | | -5x^2-16=x-2-8x^2 | | 7[1-(3c+9-2c-6)]=-14c | | 4(k-3)=2-(2k-k) | | 17-(4m+8)=4+2m-19 | | 5x^4-30x^3+30x^2=0 | | 2(15+6y)+6y=-12 | | 22-42=(x-1)-4 | | 3x-12=5x-18 | | 5a^2-21a-14=6 | | 3y(3y+8)=9 | | -4-6=12 | | 3x-16=x+89 | | 2n^2=-14+11n | | 2e^3x-4+8=56 | | 2y+4=8y-8 | | 5=-2n+8+3 | | x/6=10.5 | | -8(-8+n)-6(7n-3)=54 | | 3n^2-1=-2n | | 6(2m-5)+3m=15m-10 | | a=3.14(5625) | | 9x+15=-36 | | 9r-7r=12 | | -3(7b-5)=99 | | 1/2,-2,1 | | -34=4a-2a | | h-3.5=7.6 |